PENGUKURAN KUALITAS LAYANAN JARINGAN KABEL SERAT OPTIK LINK BENCULUK-JIMBARAN - Putu Ratih Devyanti; Gede Sukadarmika; Komang Oka Saputra (Program Studi Teknik Elektro UNUD, 2021)
Optical fiber is a telecommunication transmission medium that has a high bandwidthand bit rate so that it can meet the needs of today's information services with high reliability andefficiency. Optical fiber applications are increasingly widespread for underwater networks,terrestrial networks, metropolitan and regional network coverage, also small-scale networksincluded. Optical fiber communication system has internal and external factors that affect thequality of network performance. Those factors possibly able to reduce the performance of theoptical fiber networks. Then, can cause attenuation and other transmission losses. In an effortto prevent sudden and significant deterioration in the quality of a network, it is necessary tocarry out periodic maintenance activities such as measuring the quality of scheduled fiber opticcable network services. These maintenance activities can help determine the decision toincrease network capacity at a later date. The service quality parameters that often measuredare the attenuation of the transmission and the received signal power (power receive). Thisstudy examines the measurement of attenuation of the Benculuk-Jimbaran fiber optic cableusing OTDR EXFO FTB-150. The measurement results of 8 idle cores were analyzed usingOptisystem 7.0 and the calculation of total attenuation and receive sensitivity. Themeasurement results of core 1 to core 12 have total attenuation ranging from 29, 942 dB -30.654 dB at a distance of 169, 646 km - 170, 323 km. The value of power received on cores 1to 12 has a value ranging from -17,339 dBm - 18,204 dBm, where all idle cores fulfill the receivesensitivity requirements set by ITU-T, which is greater than -28 dBm. Based on the performance analysis according to total attenuation and power receive parameters, the Benculuk-Jimbaranfiber optic link network has good performance quality.